Biomonitoring in two contrasting catchments - Maseti, Pumza Penelope (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2006)
The introduction of instream biological monitoring to water resources management has been an increasing trend world-wide. This monitoring uses biological field assessments of instream biota such as macroinvertebrates, fish and riparian vegetation as an integrated and sensitive tool for diagnosing the condition of the ecosystems and assessing ecological impacts. Biomonitoring information has become an important component in the overall assessment of water resources and is used to drive and direct processes of decision-making and management of water resources. The River Health Programme (RHP) was initiated in South Africa to serve as a source of information regarding the ecological status of river systems, in order to support rational management of these natural resources. In this study, biomonitoring indices (SASS5 and FAII) were used to assess the present ecological status of two rivers located in contrasting catchments of the Eastern Cape. The first river is the Buffalo River located in an urban and industrialized catchment. The second river is the Inxu River draining a rural and afforested catchment. SASS5 was used successfully in both rivers and the results based on water quality and SASS5 indicated that most sites selected on the upper catchment of the Buffalo River have a fair water quality with most sites selected on the lower catchment having a poor water quality. The Inxu River sites (both upper and lower catchment) based on SASS5 and water quality results have a good to fair water quality. The majority of sites sampled on both rivers systems had very low FAII scores and fell within a critically modified water quality category. This result may be due to the fact that these rivers have low fish diversities (either low natural diversity or low diversity due to the presence of alien fish species), poor water quality or inadequate sampling methods. Observations from this study suggest that this index may not be suitable for rivers with low fish diversity. A fish index that is usable to all ecoregions of South Africa with minor adaptations to suit local conditions is still needed, as the present FAII index does not meet these requirements.
Keywords: Water quality biological assessment -- South Africa; Water quality management -- South Africa; Rivers -- South Africa; Freshwater fishes -- South Africa